Beneficial Effects of Palmitoylethanolamide on Expressive Language, Cognition, and Behaviors in Autism: A Report of Two Cases. (29th September 2015) - Antonucci, Nicola; Cirillo, Alessandra; Siniscalco, Dario
Abstract : Introduction . Autism spectrum disorders are defined by behavioral and language atypias. Growing body of evidence indicates inflammatory mediators may contribute to the condition. Palmitoylethanolamide (PEA) is naturally occurring and has been available as a nonprescription medical food supplement in Europe since 2008. PEA has been tested in thousands of human subjects without any noted significant side effects. Here we report the first cases of the administration of PEA to two children with autism. Case Presentations . The first 13-year-old male child (Subject 1) presented with a total IgE of 572 IU/mL (nl < 200) and with low mature CD57 + natural killer cell counts (32 cells/ µ L; nl = 60–300 cells/ µ L) and with significant eczema and allergic stigmata. Expressive language, as measured by mean length of utterance, and overall autism severity as measured by the Childhood Autism Rating Scale, Second Edition, improved significantly. Atopic symptoms diminished. No side effects were reported. The second male child, age 15 (Subject 2), also displayed noticeable and rapid improvements in cognitive, behaviors, and sociability. Conclusion . Currently, there is no definitive treatment for autism condition. Palmitoylethanolamide could be an effective treatment for autism syndrome. We propose appropriate double-blind clinical trials to further explore palmitoylethanolamide efficacy and safety.